(untitled) (Praxis Educativa, 2025)
The purpose of this article is to describe the strategy developed for the implementation of the Supervised Professional Practice (PPS) at the School of Sociology of the National University. It was carried out using a qualitative approach, which includes documentary analysis techniques, focus group and survey, and Sociology students and teachers participated. Based on the analysis, the general characteristics of the PPS process are defined, and the responsibilities/commitments of the professors in charge of the course, of the students enrolled in the course and of the institutions receiving the practice are established. It is also concluded that the PPS is a learning and professional development process that allows students to approach the professional field.